Blood and chocolate eaudiobook - Klause, Annette Curtis (Recorded Books Inc., 1997)
Vivian Gandalon is a teen-aged werewolf with problems. Her father, the pack leader, was killed in a fire, and so the pack is in disarray. The young male members of the squabbling pack howl for her, but still she feels alienated and alone. To be more than human is a lonely thing. Vivian longs to have friends and fit in at school. She yearns to escape her legacy of violence and forbidden appetites, but the beast within her longs for something elementally deep and rich. She glories in her ability to change from woman to wolf. How can she choose between being human or beast? She fiercely hopes that her relationship with a kind and sensitive meat-boy, a human, will help her find some answers. Talented narrator Alyssa Bresnahan casts a spell over listeners as she becomes the beautiful and sensuous young werewolf princess. This suspenseful, haunting, and magical tale is best read by the light of the full moon.